2023
DOI: 10.3390/jcm12124136
|View full text |Cite
|
Sign up to set email alerts
|

Lactate to Albumin Ratio for Predicting Clinical Outcomes after In-Hospital Cardiac Arrest

Abstract: In-hospital cardiac arrest (IHCA) is associated with high mortality and poor neurological outcomes. Our objective was to assess whether the lactate-to-albumin ratio (LAR) can predict the outcomes in patients after IHCA. We retrospectively screened 75,987 hospitalised patients at a university hospital between 2015 and 2019. The primary endpoint was survival at 30-days. Neurological outcomes were assessed at 30 days using the cerebral performance category scale. 244 patients with IHCA and return of spontaneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…[37] Furthermore, compared with OHCA patients, IHCA patients had higher CRP and lower albumin levels, which correlated with patient outcomes. [8,32] Therefore, the distinctive high CRP and low albumin levels in IHCA patients, as opposed to those in OHCA patients, may be indicative of prognosis, aligning with the findings of the present study.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…[37] Furthermore, compared with OHCA patients, IHCA patients had higher CRP and lower albumin levels, which correlated with patient outcomes. [8,32] Therefore, the distinctive high CRP and low albumin levels in IHCA patients, as opposed to those in OHCA patients, may be indicative of prognosis, aligning with the findings of the present study.…”
supporting
confidence: 90%
“…The albumin level demonstrated an AUC of 0.663 (95% CI: 0.600-0.722; P= 0.004) for predicting favorable neurological outcomes. [32] CAR, a novel marker of systemic inflammation, has been associated with clinical prognoses in various diseases. [33,34] In patients with stable angina pectoris, a high CAR was linked to significant coronary artery disease.…”
mentioning
confidence: 99%
“…Wang et al reported LAR was significantly associated with 14-day, 28-day and 90-day all-cause mortality in critical patients with acute myocardial infarction [ 16 ]. Haschemi et al [ 17 ]. used this indicator to predict survival at 30-days in patients with in-hospital cardiac arrest and found that the prognostic performance of LAR was superior to that of a single measurement of lactate or albumin for predicting survival after in-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%